2018
DOI: 10.1002/cam4.1683
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of patients with gastric neuroendocrine tumors: A population‐based study

Abstract: BackgroundDespite its rarity, studies have shown the incidence of gastric neuroendocrine tumors (G‐NETs) is increasing. This study investigated the risk factors affecting the survival of G‐NETs patients and their prognosis over time.MethodA retrospective analysis of 506 G‐NETs patients who underwent surgery for nonmetastatic disease from the Surveillance, Epidemiology and End Result database from 1988 to 2011 was conducted. Multivariate Cox regression analyses identified the prognostic factors affecting overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…GNENs were an orphan disease and accounted for 6.9% of all the GEP-NENs, representing 0.3-1.8% of all gastric malignancies [17][18][19]. Based on the up-to-date SEER database, our study revealed that the incidence of GNENs has increased gradually in the past 4 decades, consisting with the previous study [1,2,17].…”
Section: Discussionsupporting
confidence: 74%
“…GNENs were an orphan disease and accounted for 6.9% of all the GEP-NENs, representing 0.3-1.8% of all gastric malignancies [17][18][19]. Based on the up-to-date SEER database, our study revealed that the incidence of GNENs has increased gradually in the past 4 decades, consisting with the previous study [1,2,17].…”
Section: Discussionsupporting
confidence: 74%
“…PDGNENs are rare tumors that are highly malignant, accounting for 6.9% of gastroenteropancreatic neuroendocrine tumors and 0.3%-1.8% of all malignant gastric tumors[ 9 , 10 ]. According to the Korean literature, PDGNENs account for 2.84% of all NENs and 40% of G-NENs[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, given the rarity and indolent biological behavior of GEP-NETs, most studies on GEP-NETs are based on a small (or very small) number of cases in single institutions. [8][9][10][11] In addition, population-based studies have never specifically targeted GEP-NETs but rather only addressed the issue of NETs in a single gastrointestinal tract site (eg, stomach, 12 colon, 13 small intestine, 14 appendix, 15 or pancreas 16 ). Therefore, in this study, we performed a population-based study using the information in the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) Program to systematically analyze the epidemiologic, clinical, and prognostic characteristics of GEP-NETs.…”
Section: Introductionmentioning
confidence: 99%